Islamic Banking: A Controversial Position of the Christian Association of Nigeria on Ethical Financial Services and Economic Sabotage - Tijjani Muhammad; Adam Muhammad Abubakar; Abdulhamid Abdullahi Adam (IAIN Padangsidimpuan, 2022)
The Central Bank of Nigeria approved the license of Non-interest financial institutions in the country in 2012. The approval has generated many issues and religious arguments everywhere in the country. Some supported the initiative to address poverty and financial exclusion, while others perceived Islamizing the financial sector. The study adopted a survey approach, while the questionnaires used and analyzed public perception, specifically in the Plateau State, Nigeria, using Structural Equation Modeling (SEM). The primary data survey questionnaire got 360 respondents. Some feel sensitive enough to oppose the system that is not imposed on any religious or ethical background, while others criticize the entire process of Islamic Banks in Nigeria. The study found that Islamic banks are established based on the fundamental Islamic teachings and originated from the Qur'an and the authentic Prophet Muhammad's teachings, which challenged some conventional financial institutions' practices that indicate a clear note of avoidance of such conventional facilities. Further, indicate that the Christian Association of Nigeria is sabotaging the momentum of Non-interest financial institutions through religious hate, and ignorance and sabotaging government policy to prevent the institutional contribution toward national development and economic growth in the country; using different approaches to frustrate the funding process of some government projects through Non-interest financial institutions. The paper recommends that regulatory bodies of financial institutions, specifically the Central Bank of Nigeria, should clear misunderstandings of the Christian Association of Nigeria towards national development, create awareness, and avoid discrimination in service delivery by pinpointing Islamic banking in the county.